The Relationship Between Environmental Factors and the Incidence of Diarrhea, as well as Prevention Education for Patients at the Arjasari Community Health Center - Nurhakim, Agung; Emelia, Rida (Jurnal Infokes, 2026)
Diarrhea is a public health problem characterized by a change in stool characteristics to soft or liquid, accompanied by an increase in the frequency of defecation to more than three times in a 24-hour period. Environmental aspects such as water quality, drainage systems, and waste management contribute significantly to the occurrence of diarrhea. This study aims to analyze the relationship between environmental factors and the incidence of diarrhea in the community in the working area of the Arjasari Community Health Center, Bandung Regency. This study applies a descriptive quantitative design with a cross-sectional approach. A questionnaire was distributed to 60 participants who met the inclusion criteria. The data obtained included sociodemographic characteristics, level of knowledge about diarrhea, and environmental conditions (availability of clean water, sewage system, and waste disposal facilities). The majority of participants were male (63.3%), with the highest level of education in the kindergarten/elementary school category (46.7%), and most were unemployed (75%). The community’s level of knowledge about diarrhea was mostly in the moderate category (71.4%). Environmental factors are associated with the incidence of diarrhea. Clean water facilities that meet standards of adequacy are more prevalent among the 5–12 age group (75%), while facilities that are not adequate are more prevalent among adults aged 19–45 (66.7%). Most sewage systems are in good condition (73.3%), and waste disposal facilities are generally adequate (81.7%). Diarrhea cases are related to environmental factors, particularly the quality of clean water supply, sewage systems, and waste management. Efforts to prevent diarrhea require improvements in sanitation infrastructure and increased public education to prevent diarrhea through public health service facilities.